Advertising Outlays under Oligopoly - Jastram, Roy W. (The Review of Economics and Statistics, 1949)
petition in the narrow sense of the term would appear to be unimportant from a public policy point of view. The real monopoly problems are associated with the large and such a is typically in competition with a few rivals. (2) A large buyer (or seller) can under certain circumstances enforce something like pure competition on his small suppliers (or customers). In the distributive trades highly routinized, inefficient and inflexible performance of function has been changed to the very considerable advantage of consumers by the penetration of large mass distributors. The existence of a large number of small competitors does not necessarily spell efficiency nor does the emergence of the large necessarily imply consumer exploitation. (3) Static analysis, using the few variables customarily considered in the economics of the firm and operating under assumptions of profit maximization, takes us a very little way toward that understanding of the behavior of large firms necessary to effective public policy in this area.